2016
DOI: 10.19072/ijet.65255
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Some Physical Properties of Rapeseed

Abstract: Abstract-Rapeseeds (Brassica napus oleifera L.) were analyzed for some physical properties production in Kırklareli province. Also some physical properties of rapeseed such as seed moisture content, length, diameter, mass of single seed, thousand seed mass, geometric mean diameter, sphericity, seed volume, density, accumulation angle and friction coefficient have been determined. Kernel moisture, thousand kernel mass, plant length, plant stem diameter, yield of the harvested crop were determined as 8.34 %, 4.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…[21] have found that the smallest coefficient of friction of grain of rapeseed on the steel sheet (0.273) is approximately the value obtained in these studies. The research results [22] for coefficient of friction on galvanized substrates (0.318), aluminum (0.305) and stainless steel sheet (0.288) are similar to the values published in this paper. The results of these studies for friction coefficients differ from the results [6], only in that the coefficient of friction on the surface of galvanized sheet is greater than the coefficient on the plastic substrate.…”
Section: Resultssupporting
confidence: 87%
“…[21] have found that the smallest coefficient of friction of grain of rapeseed on the steel sheet (0.273) is approximately the value obtained in these studies. The research results [22] for coefficient of friction on galvanized substrates (0.318), aluminum (0.305) and stainless steel sheet (0.288) are similar to the values published in this paper. The results of these studies for friction coefficients differ from the results [6], only in that the coefficient of friction on the surface of galvanized sheet is greater than the coefficient on the plastic substrate.…”
Section: Resultssupporting
confidence: 87%
“…Işık ve İzli (2016) found that the sphericity increased with the increase of moisture in the yellow split lentil. Baran et al (2016) determined the sphericity of canola as 88% for 8.34% moisture content. The sphericity of canola seeds on the contrary of flatness, firstly decreased and then increased as the moisture content increased.…”
Section: Table 1 Physical Properties Of Canola Seedsmentioning
confidence: 99%
“…Işık veİzli (2016) reported that the thickness, diameter, arithmetic and geometric diameter increased in the yellow split lentil as the moisture increased at 5 different moisture values Baran et al (2016). found that length, width and mean geometric diameter values in canola with 8.34% moisture content as 2.35 mm, 1.93 mm and 2.07 mm, respectively.…”
mentioning
confidence: 99%